Celebrated Crimes (Complete) - Dumas, Alexandre, 1802-1870 (Salt Lake City, UT : Project Gutenberg, 2004)
"Celebrated Crimes (Complete)" by Alexandre Dumas is a historical account written during the early 19th century. This collection presents a series of narratives centered around infamous historical crimes, intertwining facts with dramatic storytelling. Dumas selects notorious figures and events, such as the Borgia family, to explore themes of power, ambition, and moral ambiguity. At the start of this work, we encounter the prologue discussing the dying moments of Lorenzo de' Medici and his spiritual confrontation with the Dominican friar Savonarola, who challenges Lorenzo to consider his sins and the state of Florence. This opening sets the tone for the subsequent exploration of notorious characters and their crimes, as Dumas provides both historical context and moral insight, emphasizing the interplay between personal ambition and the greater political landscape. The introduction signals the depth and complexity of the narratives to follow, inviting readers to delve into the violent and intricate histories that shaped Europe. (This is an automatically generated summary.)
The Borgias -- The Cenci -- Massacres of the South -- Mary Stuart -- Karl-Ludwig Sand -- Urbain Grandier -- Nisida -- Derues -- La Constantin -- Joan of Naples -- The man in the iron mask (essay) -- Martin Guerre -- Ali Pacha -- The Countess de Saint Geran -- Murat -- The Marquise de Brinvilliers -- Vaninka -- The Marquise de Ganges.
Release date is 2004-09-22
David Widger
Keywords: Criminals -- Biography; Crime